Use of Cocopeat and Zeolite as a Seedling Media for Cocoa and Its Response to Some Levels of Available Water - Leizy Free Agustin F; Soetanto Abdoellah; Cahyoadi Bowo (Indonesian Coffee and Cocoa Research Institute, 2010)
Up to now, cocoa pod husk is commonly collected as heap nearby processing facilities or in the field and being considered as waste. To minimize the negative impact of the husks and to obtain added value an effort to develop the husk into granule fertilizer has been carried out. Fresh cocoa pod husk was hulled to obtain organic paste, then mixed with 5% zeolite and 5% rock phosphate powder (w/w). The mixture was kept for 2 weeks prior to granulation. The granules were characterized for their physical and chemical properties. Agronomic tests of the granules were conducted on coffee and cocoa seedlings as indicator plants. The tests were set according to completely randomized design and the treatments were arranged factorially. The evaluated treatments consisted of rates of granules and rates of inorganic fertilizer applications. The granules were applied at 7 levels: 0, 5, 10, 15, 20, 25 and 30 g/seedling. The granule treatments were combined with application of inorganic compound fertilizer at rates of 0 and 2 g fertilizer/application of N-P-K compound fertilizer of 15-15-15. The inorganic fertilizers were applied four times during experiment. The results indicated that the granule has high water holding capacity; cations exchange capacity, and high content of organic carbon and phosphorus. The growth of coffee and cocoa seedlings increased due to application of granules derived from cocoa pod husk. Responses of coffee and cocoa seedlings to granule application conformed to quadratic equations. The optimum application rate of granules was 14.5 g/seedling for Robusta coffee seedlings and 14.6 g/seedling for cocoa seedlings. Granule application may replaced role of inorganic fertilizer to increase growth of cocoa and coffee seedling.Key words: Cocoa pod husk, organic waste, seedling growth, zeolite, rock phosphate, minerals, Theobroma cacao L., Coffea canephora.